Gauging the threat of invasive species to UNESCO world heritage sites relative to other anthropogenic threats - Marc William Cadotte; Mohamed Alabbasi; Sara Akib; Pruthuvie Chandradhas; Joanne Gui; Kelly Huang; Adrian Li; David M. Richardson; Ross T. Shackleton (Biological Invasions, 2024)

Biological invasions in World Heritage Sites: current status and a proposed monitoring and reporting framework - Ross T. Shackleton; Bastian Bertzky; Louisa E. Wood; Nancy Bunbury; Heinke Jäger; Remco van Merm; Christian Sevilla; Kevin Smith; John R. U. Wilson; Arne B. R. Witt; David M. Richardson (Biodiversity and Conservation, 2020)
UNESCO World Heritage Sites (WHS) are areas of outstanding universal value and conservation importance. They are, however, threatened by a variety of global change drivers, including biological invasions. We assessed the current status of biological invasions and their management in 241 natural and mixed WHS globally by reviewing documents collated by UNESCO and IUCN. We found that reports on the status of biological invasions in WHS were often irregular or inconsistent. Therefore, while some reports were very informative, they were hard to compare because no systematic method of reporting was followed. Our review revealed that almost 300 different invasive alien species (IAS) were considered as a threat to just over half of all WHS. Information on IAS management undertaken in WHS was available for fewer than half of the sites that listed IAS as a threat. There is clearly a need for an improved monitoring and reporting system for biological invasions in WHS and likely the same for other protected areas globally. To address this issue, we developed a new framework to guide monitoring and reporting of IAS in protected areas building on globally accepted standards for IAS assessments, and tested it on seven WHS. The framework requires the collation of information and reporting on pathways, alien species presence, impacts, and management, the estimation of future threats and management needs, assessments of knowledge and gaps, and, using all of this information allows for an overall threat score to be assigned to the protected area. This new framework should help to improve monitoring of IAS in protected areas moving forward.

Invasion syndromes: a systematic approach for predicting biological invasions and facilitating effective management - Ana Novoa; David M. Richardson; Petr Pyšek; Laura A. Meyerson; Sven Bacher; Susan Canavan; Jane A. Catford; Jan Čuda; Franz Essl; Llewellyn C. Foxcroft; Piero Genovesi; Heidi Hirsch; et al. (Biological Invasions, 2020)
Our ability to predict invasions has been hindered by the seemingly idiosyncratic context-dependency of individual invasions. However, we argue that robust and useful generalisations in invasion science can be made by considering “invasion syndromes” which we define as “a combination of pathways, alien species traits, and characteristics of the recipient ecosystem which collectively result in predictable dynamics and impacts, and that can be managed effectively using specific policy and management actions”. We describe this approach and outline examples that highlight its utility, including: cacti with clonal fragmentation in arid ecosystems; small aquatic organisms introduced through ballast water in harbours; large ranid frogs with frequent secondary transfers; piscivorous freshwater fishes in connected aquatic ecosystems; plant invasions in high-elevation areas; tall-statured grasses; and tree-feeding insects in forests with suitable hosts. We propose a systematic method for identifying and delimiting invasion syndromes. We argue that invasion syndromes can account for the context-dependency of biological invasions while incorporating insights from comparative studies. Adopting this approach will help to structure thinking, identify transferrable risk assessment and management lessons, and highlight similarities among events that were previously considered disparate invasion phenomena.

Distribution and socio-ecological impacts of the invasive alien cactus Opuntia stricta in eastern Africa - Ross T. Shackleton; Arne B. R. Witt; Francis M. Piroris; Brian W. van Wilgen (Biological Invasions, 2017)

Chromolaena odorata (Siam weed) in eastern Africa: distribution and socio-ecological impacts - Ross T. Shackleton; Arne B. R. Witt; Winnie Nunda; David M. Richardson (Biological Invasions, 2017)

Knowledge, perceptions and willingness to control designated invasive tree species in urban household gardens in South Africa - Charlie M. Shackleton; R. T. Shackleton (Biological Invasions, 2016)

Stakeholder perceptions and practices regarding Prosopis (mesquite) invasions and management in South Africa - Ross T. Shackleton; David C. Le Maitre; David M. Richardson (Ambio, 2015)

Morphology of physiologically characterised ventral cochlear nucleus stellate cells - A. R. Palmer; M. N. Wallace; R. H. Arnott; T. M. Shackleton (Experimental Brain Research, 2003)